Vertebroplasty and Kyphoplasty in Vertebral Osteoporotic Fractures - Aparisi, Francisco (Seminars in Musculoskeletal Radiology, 2016)
Vertebroplasty and kyphoplasty are minimally invasive treatments and indispensable tools in the treatment of osteoporotic compression fractures. This method of treatment is performed using fluoroscopy or a scanner control an access via the pedicle or the posterolateral angle of the vertebral body. Vertebroplasty requires a smaller caliber needle than kyphoplasty, so it is technically easier. Vertebroplasty uses high-pressure injection, whereas in kyphoplasty the injection is held at low pressure, which together with the effect of compression on the bone that the balloon produces reduces the risk and rate of cement leakage. Vertebroplasty is effective in managing osteoporotic compression vertebral fractures, with improvement in pain and quality of life in the immediate postoperative period and over the medium term.Both techniques have a very low complication rate. There is no consensus on whether the emergence of new fractures in the cases treated by vertebroplasty and kyphoplasty are related to mechanical variations that were introduced or is a complication related to the age and evolution of the patient's osteoporosis. Even with this risk of new fractures, the improvement in quality of life obtained after vertebroplasty and kyphoplasty treatment is worthwhile. The benefits outweigh the risks.
Keywords: vertebral fractures; vertebroplasty; kyphoplasty